Konstruksi Pengetahuan dalam Perspektif Metodologi Program Riset Ilmiah Imre Lakatos - Theguh Saumantri (LPPM IAIN Sorong, 2022)
The purpose of this study is to describe imre Lakatos' analysis of the concept of The Methodology Scientific Research Program which contributes to the contextualization of contemporary knowledge and passes down the tradition of research to Islamic science. In philosophical discourse, knowledge is the consciousness of man in search of an objective truth. This research is a library research with a philosophical approach. The conclusions in this study explain that in imre lakatos thinking science is a series of interrelated theories that in its development always have a continuous character (continuity) The prototype of the Lakatos Research Program is an engineering program to obtain science consisting of negative heuristics and positive heuristics and the research program initiated by Lakatos is a formulation of the procession of scientific discoveries, so it is hoped that the practice can be followed.